2015
DOI: 10.1111/petr.12527
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and deficiency in pediatric renal transplant recipients

Abstract: Vitamin D deficiency is prevalent in the pediatric CKD population. Recognizing that renal transplant recipients have CKD, we assessed the prevalence of vitamin D insufficiency and deficiency in pediatric renal transplant recipients, compared to a healthy pediatric population. We prospectively studied 25(OH)D levels in 29 pediatric renal transplant recipients and 45 control patients over one yr. The overall prevalence of vitamin D insufficiency and deficiency was common in both populations, at 76% (95% CI: 61, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Little research has compared the 25(OH)D serum levels between patients undergoing KT and the healthy population. Our findings coincide with those of Ebbert et al, who analyzed a pediatric population, reporting the presence of hypo D in patients undergoing KT as well as control groups 15. However, our findings showed that patients undergoing KT had a higher prevalence of deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Little research has compared the 25(OH)D serum levels between patients undergoing KT and the healthy population. Our findings coincide with those of Ebbert et al, who analyzed a pediatric population, reporting the presence of hypo D in patients undergoing KT as well as control groups 15. However, our findings showed that patients undergoing KT had a higher prevalence of deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormalities in mineral metabolism including disturbances in serum calcium, phosphorus, parathyroid hormone (PTH), and vitamin D stores, are common in children following kidney transplant and increase the risk for growth delay and osteopenia or rickets. [40][41][42] Determinants of growth following transplant include age at the time of transplant, exposure to glucocorticoids, allograft function, and administration of recombinant human growth hormone (rhGH). Children under the age of 6 years have increased growth rates following transplant compared to older children.…”
Section: Growth and Development Short Stature And Bone Healthmentioning
confidence: 99%
“…The 25(OH)D levels were low before and after transplantation in this study with no apparent association with FGF23 or αKlotho. It was reported that 25(OH)D deficiency was also present in pediatric CKD patients, 36 and pediatric kidney transplant patients, 37 which was associated with graft function. 38 The present results are consistent with this, but the association with graft function is unclear.…”
Section: Discussionmentioning
confidence: 99%